2018
DOI: 10.1088/1361-6587/aae16b
|View full text |Cite
|
Sign up to set email alerts
|

Electron-CO excitation and ionization cross sections for plasma modeling

Abstract: The influence of the internal energy content, either vibrational or electronic, on the probability of CO elementary processes induced by electron-impact is investigated. In particular the vibronic excitations of the first singlet state of the CO spectrum, A 1 Π, are derived in the framework of the similarity approach, characterizing also the radiative properties to the ground electronic state. Moreover the ionization of the ground state to the first three states of the molecular ion are calculated with the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, it is shown that even in swarm Fig. 8 BEB cross sections for electron impact ionization of the CO(X 1 Σ + g ) ground state from v=0 (dashed line) and from v=40 (dotted line) and total ionization cross section for CO(a 3 Π) calculated by Laricchiuta et al [217]. The insertion shows the detail of the different threshold energies conditions inelastic and superelastic collisions involving rotationally excited levels, as well as superelastic collisions with the first vibrational excited level, have to be taken into account to accurately calculate the electron energy distribution function.…”
Section: Comentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, it is shown that even in swarm Fig. 8 BEB cross sections for electron impact ionization of the CO(X 1 Σ + g ) ground state from v=0 (dashed line) and from v=40 (dotted line) and total ionization cross section for CO(a 3 Π) calculated by Laricchiuta et al [217]. The insertion shows the detail of the different threshold energies conditions inelastic and superelastic collisions involving rotationally excited levels, as well as superelastic collisions with the first vibrational excited level, have to be taken into account to accurately calculate the electron energy distribution function.…”
Section: Comentioning
confidence: 96%
“…This implies that the elastic and rotational cross sections proposed in [209] are not accurate per se, but can nevertheless be used in the consistent set to obtain an accurate calculation of the EEDF with a two-term Boltzmann solver. The CO electron impact ionization cross sections of the CO(X 1 Σ + g ) ground state (vibrational state resolved) and of the CO(a 3 Π) electronic excited state were calculated by Laricchiuta et al [217] by using the binary-encounter-Bethe (BEB) model. The corresponding results are reported in Fig.…”
Section: Comentioning
confidence: 99%
“…In Ref. [29] ab initio unrestricted Hartree Fock (UHF) calculations were performed, with the aug-cc-pVTZ basis set, in the D2h symmetry point group at the equilibrium geometry of the metastable N…”
Section: Resultsmentioning
confidence: 99%
“…The method, attractively combining simplicity and accuracy, was successfully and extensively applied to many atomic and molecular systems in the ground state, including fusion-relevant species containing heavy elements as beryllium/tungsten oxides, hydrides and nitrides [27], and also to the ionization of low-lying excited states of carbon, nitrogen and oxygen atoms [28]. Here, the results recently obtained for to the metastable states of N 2 and CO [29] are reviewed and new results for H 2 molecule are presented, discussing the comparison with other theoretical methods.…”
Section: Introductionmentioning
confidence: 96%
“…During gas metal arc welding in the CO 2 shielding gas, CO 2 dissociates to CO and O 2 in the arc since its dissociation degree significantly rises at 2000 K [37]. CO reacts with the plasma in the arc [38,39], and since CO ionization energy is higher than that of CO 2 , the arc voltage increases and hence the arc current.…”
Section: Resultsmentioning
confidence: 99%